2015
DOI: 10.1002/adma.201501425
|View full text |Cite
|
Sign up to set email alerts
|

Inkjet Printing of Regenerated Silk Fibroin: From Printable Forms to Printable Functions

Abstract: A formulation of regenerated silk fibroin solution that can be easily functionalized and inkjet printed on numerous surfaces is developed. As an example, the inks can be printed on laboratory gloves that change color when exposed to bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
179
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 191 publications
(180 citation statements)
references
References 44 publications
0
179
0
1
Order By: Relevance
“…[ 34 ] It has also been reported that printed silk structures can signifi cantly retain the activity of enzymes (e.g., horse radish peroxide), making it an attractive choice of scaffold. [ 33 ] However, in these examples, the structures formed were very thin and remained bound to a substrate and so full conversion to Silk II was not required (in one study partial conversion due to the shear stress involved during printing was suggested). [ 34 ] Here, in order to ensure a rigid detachable scaffold we instead for the fi rst time employ reactive inkjet printing (RIJ) to allow chemical treatment with methanol to the Silk II form.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 34 ] It has also been reported that printed silk structures can signifi cantly retain the activity of enzymes (e.g., horse radish peroxide), making it an attractive choice of scaffold. [ 33 ] However, in these examples, the structures formed were very thin and remained bound to a substrate and so full conversion to Silk II was not required (in one study partial conversion due to the shear stress involved during printing was suggested). [ 34 ] Here, in order to ensure a rigid detachable scaffold we instead for the fi rst time employ reactive inkjet printing (RIJ) to allow chemical treatment with methanol to the Silk II form.…”
mentioning
confidence: 99%
“…The potential to expand upon this initial demonstration is great, not least due to the large number of materials (e.g., drugs, enzymes, and antibodies) that can be encapsulated within the silk scaffold. [ 33,34,38,42,58 ] This will, for example, in the future allow straightforward investigations of new enzymatic reactions not reliant on peroxide fuel to power devices, addition of selective cargo binding chemistry to the inactive segment, and incorporation of magnetic materials to allow steering by external fi elds. We also note that RIJ technology is subject to rapid development, which will open up the potential to further miniaturize devices.…”
mentioning
confidence: 99%
“…Inkjet bioprinting is widely explored in the field of tissue engineering due to their unique characteristics of noncontact printing, high-throughput efficiency, automation, versatility, resolution, and possibility of parallel printing. This technology has been used to print a variety of compounds in prescribed 2D patterns, including growth factors [119], proteins [5], polymers [85], nanoparticles [190] and drugs [94]. The capability of inkjet bioprinting to print mammalian cells with high accuracy, and little or even no reduction of cell viability, was also demonstrated using different cell types, such as embryonic rat motoneurons [206], human microvascular endothelial cells [34], mouse embryonic fibroblasts [194], and retinal ganglion cells [12].…”
Section: Inkjet Bioprintingmentioning
confidence: 99%
“…Other examples of silk-based "bio-inks" include the combination of silk and HRP, which has the ability to preserve enzymatic activity, and silk with gold nanoparticles. The silk-gold ink was used for color engineering and surface plasmonic applications, where, when a green laser light was directed onto a paper printed with the ink, a topographical thermal distribution pattern was revealed on the printed pattern (13).…”
Section: O M M E N T a R Ymentioning
confidence: 99%